Telecommunications signalling - Manterfield, Richard J. (London, United Kingdom Institution of Electrical Engineers, 1999)
The following topics are dealt with: signalling system; CCSS7 message transfer part; signalling connection control part; ISDN; mobile communication; intelligent network; DSS1 network layer; private networks; broadband access signalling; Internet protocols; channel associated signalling; and inter-PABX signalling.
Electronic reproduction.
Keywords: Signal processing; Electronic books